Pembangunan pertanian di Desa Joho Kecamatan Mojolaban Kabupaten Sukoharjo - Imani, Cahya Sekar; Ariefin, Damar; Rahmadini, Fadistika; Hatmadiya, Listya; Imaduddin, Naufal (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Various efforts have been made by the government to increase agricultural productivity and farmer welfare. Factors that cause the decreasing interest of young workers in the agricultural sector include the agricultural sector being considered less valuable, risky, income being less stable and sustainable, decreasing agricultural land area, diversity of companies and lack of development of both agricultural and non-agricultural industries in villages, failure to manage many farms, lack of political support for young farmers or prospective farmers and the tendency of youth perspectives in the postmodern era. Findings: National agricultural sector development efforts can synergize with village development efforts to improve them. Rural and agricultural development planning must be able to ensure that current development activities do not pass on poor conditions to future generations. Sustainability assessment explains the principles of sustainability, whether and to what extent the initiative allows the area to be sustainable. Methods: This study uses a descriptive qualitative method with primary and secondary data bases through data collection techniques using interview techniques. Conclusion: Joho Village has quite large agricultural potential, especially in rice and corn commodities. This potential is supported by the existence of human resources that support the agricultural sector, namely the population of Joho Village who work in agriculture as much as around 70%. The existing problems regarding the cultivation of rice commodities that had experienced several obstacles at certain times, namely the attack of rice plants by KB disease, where the cause and solution of this disease are not yet known, so that rice production in Joho Village often experiences a drastic decline. Assistance from the local government is still considered less than optimal, such as assistance in subsidized fertilizers, seeds, and others.